ANALYSIS OF THE BADUY COMMUNITY'S SOCIAL RESPONSE TO THE PRESENCE OF TOURISTS - Dewi Septiani; Ripa Eka Nurwanda; Tahta Irmanda; Eneng Liah Khoiriyah; Iim Khairunnisa (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2023)
This research aims to analyze and know how Baduy community responds to tourists who visit their area. The method used in this research is descriptive qualitative by focusing on the response of Baduy community towards tourists and the changes that occur in the Baduy tribe after the influx of tourists as the basis in this paper. Data collection technique in this research is through observation, interview, and documentation. The location of this research is in Baduy Tourism Village, Kanekes Village, Leuwidamar District, Lebak Regency, Banten Province. The result of this research shows that the response of Baduy community to tourists is very good, they accept well the tourists who come to their village. Even if there are tourists who want to know and feel how to live in Baduy, they allow tourists to stay in their homes. With the presence of tourists, they also feel helped in their economy because many tourists buy their handicrafts and crops. After the influx of tourists to Baduy, slowly there is a change that occurs in the Baduy community. This change can be seen in the outer Baduy residents who have started to recognize smart phones, social media, and other changes.